Subacute exposure of rats by metal oxide nanoparticles through the airways : general toxicity and neuro-functional effects - Oszlánczi, Gábor (Acta Biologica Szegediensis, 2010)
In order to create an animal model of human inhalational exposure by industrial metal fumes, nanoparticulate metal oxides (MnO2, CdO2, PbO) were synthesized and instilled into the trachea of rats 5 times a week for 6 weeks (metal doses per kg b.w.: 2.63 and 5.26 mg Mn; 0.04 and 0.4 mg Cd; 2 and 4 mg Pb). At the end, the rats’ body weight gain during the treatment was determined, the animals had an open field session to investigate their spontaneous motility, and finally spontaneous and stimulus-evoked cortical activity was recorded in urethane anaesthesia. Mn caused decrease of open field ambulation and rearing, Cd had no effect, whereas Pb caused decreased rearing and increased ambulation. Spontaneous cortical activity was shifted to higher frequencies with each metal. Cortical evoked potentials had lengthened latency, mainly with Mn and Cd; and increased frequency dependence with Cd and Pb but hardly with Mn. The effects proved indirectly that the metal content of the nanoparticles had access from the airways to the CNS. Our method seems suitable for modelling human nervous system damage due to inhaled nanoparticles